TANGGUNG JAWAB PENGANGKUT TERHADAP PENGIRIM BARANG ATAS KERUSAKAN TOTAL BARANG YANG DIANGKUT BERDASARKAN UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN (STUDI KASUS: PUTUSAN NOMOR 334/PDT.G/2017/PN JKT.PST) - Muhammad Alif Miftahurrahman; H.K. Martono (Fakultas Hukum Universitas Tarumanagara, 2021)
In land transportation activities there are several things that must be considered by the carrier in order to safely arrive at the destination. One of them is the inspection of the vehicle that will be used to deliver goods. Transporters often do not pay attention to vehicles from cars used for transportation activities, this is what causes accidents to cause total damage to the goods being transported. The main problems are: 1). What is the responsibility of PT Aeronusa Inti Raya for the total damage to goods transported according to Law Number 22 of 2009? 2). How did the judge determine the decision number 344 / Pdt.G / 2017 / PN Jkt.Pst for the removal of PT Aeronusa Inti Raya's responsibility for the total damage to the goods transported? This problem uses normative law research methods and uses a punitive approach, a case approach and a conceptual approach. Research shows that the transporter data must be responsible for damage to the goods transported due to an accident exploding the elf box car which is the vehicle to deliver goods belonging to PT Datascrip, PT Aeronusa Inti Raya must offer compensation to PT Datascrip and the judge's decision is not in accordance with Law Number 22 In 2009. Supposedly, transporters pay attention to the means of transportation before leaving so as to minimize accidents.